2021
DOI: 10.1016/j.abrep.2021.100359
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of lifetime substance-use disorder with family functioning, childhood victimisation, and depression, among juvenile offenders in Malaysia

Abstract: Highlights The prevalence of the lifetime history of substance use disorder in male juvenile offenders is high. The offenders highly used tobacco and amphetamine-type stimulants. The rate of victimization in juvenile offenders is high. Peer victimization and adolescent age predict lifetime substance use in juvenile offenders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 66 publications
0
9
0
1
Order By: Relevance
“…Of course, this kind of finding is not offered by studies with mono-religious samples (e.g., Eseed & Khoury-Kassabri, 2018;French et al, 2008;Khan, et al, 2020). For the rest of the articles selected, eight of them offered inter-religious comparisons as part of their findings (Carol et al, 2020;Demmrich & Akgül, 2020;Donath, et al, 2011;Klanjsek et al, 2012;Pedersen et al, 2015;Schmitt-Rodermund & Silbereisen, 2008;Seto, 2021;Wahab et al, 2021). Generally, studies that presented inter-religious comparisons supported the notion that Muslim adolescents have a lower rate of delinquency ranging from petty offences to substance abuse.…”
Section: Inter-religious Comparisonsmentioning
confidence: 99%
“…Of course, this kind of finding is not offered by studies with mono-religious samples (e.g., Eseed & Khoury-Kassabri, 2018;French et al, 2008;Khan, et al, 2020). For the rest of the articles selected, eight of them offered inter-religious comparisons as part of their findings (Carol et al, 2020;Demmrich & Akgül, 2020;Donath, et al, 2011;Klanjsek et al, 2012;Pedersen et al, 2015;Schmitt-Rodermund & Silbereisen, 2008;Seto, 2021;Wahab et al, 2021). Generally, studies that presented inter-religious comparisons supported the notion that Muslim adolescents have a lower rate of delinquency ranging from petty offences to substance abuse.…”
Section: Inter-religious Comparisonsmentioning
confidence: 99%
“…Kesukaran ini mungkin disebabkan oleh pengalaman negatif kanak-kanak (adverse childhood experience) yang mempengaruhi tingkah laku, ciri-ciri psikopati yang dimiliki, masalah ketagihan dan kesan dilabel (iaitu perasaan keterasingan dari masyarakat) (Jacobs et al, 2021;Kennedy, Edmonds, Millen & Detullio, 2019). Di Malaysia, majoriti remaja yang terlibat dengan jenayah turut melaporkan pengalaman negatif sewaktu kanak-kanak seperti pengalaman tingkah laku ganas, perceraian ibu bapa, sejarah didera atau ditinggalkan (Wahab et al, 2021;Tan, Zuraini & Noor Banu, 2019). Sesetengah mereka turut menunjukkan ciri-ciri psikopati dan risiko pengulangan tingkah laku jenayah yang tinggi (Hassan, Kendrick & Ibrahim, 2020).…”
Section: Pengenalanunclassified
“…These maltreatments are suggested to trigger the use of the substance as a coping strategy to alleviate the pain of being maltreated or indirectly by causing a criminal lifestyle that mediates contact with substance use ( 8 ). A local study by Wahab et al ( 9 ) reported that peer and sibling victimization was positively correlated with lifetime use of illicit substances. It was also reported that young women with a history of childhood sexual abuse were more likely to have psychiatric comorbidities, such as depression ( 10 ).…”
Section: Introductionmentioning
confidence: 99%